Molecular cloning and expression of the 3-chlorobenzoate-degrading genes from Pseudomonas sp. strain B13. - Weisshaar, M P (1987)
The genes specifying the utilization of 3-chlorobenzoate by Pseudomonas sp. strain B13 WR1 have been cloned by using a broad-host-range cosmid cloning system. Analysis of the catabolic products of the enzymatic reactions encoded by two hybrid cosmids, pMW65 and pMW90, by thin-layer and high-performance liquid chromatography demonstrated that both encoded the genes for the complete catabolism of 3-chlorobenzoate. Physical analysis of one of the cosmid derivatives, pMW65, by restriction endonuclease mapping and subcloning demonstrated that the pathway genes are encoded on a fragment no larger than 11 kilobases.